(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
This work seeks to investigate how media influences the social construction of reality (Berger and Luckmann, 1966), enhancing the creation of a sports culture in Brazil and the United States through television. To this end, we analyzed editions of the programs Esporte Espetacular (TV Globo) and One Team: The Power of Sports (NBC), as well as sports broadcasts from television programming in both countries. The investigation attempts to point out similarities and differences in the production, circulation, and consumption of sports audiovisual content, reconstructing new television cultural flows (Williams, 2016). We combined the methodology of bibliographic review in the field of culture (Hall, 2003; Kellner, 2001; and Bourdieu, 1989) with the Analysis of Audiovisual Materiality (Coutinho, 2016), establishing an interface between culture, sport, and audiovisual media. We found distinctions between the concept of sport in Brazil and the United States, reflecting in the content offered and the visibility of different sports.